2011
DOI: 10.1080/02188791.2011.566997
|View full text |Cite
|
Sign up to set email alerts
|

Learning, teaching, and constructing identities: ESL pre-service teacher experiences during a short-term international experience programme

Abstract: Short-term international experience programmes are a common element of English second language (ESL) teacher education in many countries. This study problematizes the belief that such programmes necessarily result in beneficial changes in pre-service teachers thinking about themselves as teachers -their beliefs, habits, and values -by exploring the experiences of eight pre-service ESL teachers from Hong Kong as they undertook a short-term international experience programme in Australia. Drawing on a theory of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 19 publications
2
21
0
4
Order By: Relevance
“…Em todas as quatro histórias, a identidade profissional em relação ao contexto de imersão ou, mais precisamente, as formas como elas são recebidas pelos anfitriões, desempenha um papel fundamental na construção de significados das variadas experiências das participantes (JACKSON, 2010;KINGINGER 2004KINGINGER , 2009PITTS, 2009;TRENT, 2011). A Princesa, uma professora estabelecida, e a Cinderella, uma professora iniciante, se esforçaram, respeitosamente, em um nível psicológicoprofissional para sustentar ou desenvolver suas identidades profissionais em resposta a determinadas circunstâncias exteriores que não eram estrangeiras, mas profissionais, ou melhor, inapropriadas (PLEWS et al, 2010).…”
Section: Aninha: Partindo Com Feedbackunclassified
See 2 more Smart Citations
“…Em todas as quatro histórias, a identidade profissional em relação ao contexto de imersão ou, mais precisamente, as formas como elas são recebidas pelos anfitriões, desempenha um papel fundamental na construção de significados das variadas experiências das participantes (JACKSON, 2010;KINGINGER 2004KINGINGER , 2009PITTS, 2009;TRENT, 2011). A Princesa, uma professora estabelecida, e a Cinderella, uma professora iniciante, se esforçaram, respeitosamente, em um nível psicológicoprofissional para sustentar ou desenvolver suas identidades profissionais em resposta a determinadas circunstâncias exteriores que não eram estrangeiras, mas profissionais, ou melhor, inapropriadas (PLEWS et al, 2010).…”
Section: Aninha: Partindo Com Feedbackunclassified
“…Cachinhos supera as dificuldades práticas de uma burocracia estranha e, também, chega a um acordo com sua supervigilante família anfitriã transformando a situação em um exercício de enriquecimento cultural (IINO, 2006). Enquanto ela está, inicialmente, desconfortável com seu senso de autoridade diminuída em sala de aula e "direitos" dos professores canadenses, ela integra suas observações e compreensão do comportamento da sala de aula canadense em sua prática e ajusta parte de sua identidade docente, pelo menos enquanto ela está no Canadá (BARKHUIZEN;FERYOK, 2006;LEE, 2009;MARX;MOSS, 2011;TRENT, 2011;WILLARD-HOLT, 2001).…”
Section: Aninha: Partindo Com Feedbackunclassified
See 1 more Smart Citation
“…The studies discovered that teachers' perceptions mainly changed in the following categories: language proficiency (Barhuizen & Feryok, 2006;Gleeson & Tait, 2012;Lee, 2009;Trent, 2011;Wang, 2014), teaching ideology (Wang, 2014), cultural awareness (Barhuizen & Feryok, 2006;Gleeson & Tait, 2012;Lee, 2009;Trent, 2011), Non-native English-speaking teachers-Native English speaking teachers (NNEST-NEST) dichotomy (Wang, 2014), personal growth (Barhuizen & Feryok, 2006;Lee, 2009), and pedagogical understanding (Barhuizen & Feryok, 2006;Lee, 2009), all of which can be connected with teachers' identity transformation.…”
Section: Effects Of Study-abroad Experience On Chinese Language Teachersmentioning
confidence: 99%
“…Finally, there have been studies showing that a short-term study abroad program may even have the opposite of the desired effect. Trent (2011) found that, for some preservice teachers from Hong Kong, short-term study abroad experiences could lead to identity conflicts and antagonistic feelings between how teaching was conceived at home versus the short-term study abroad context. In fact, it may have even led to preservice teachers reconsidering whether they still wanted to become teachers in their home countries.…”
Section: Short-term Study Abroadmentioning
confidence: 99%